Field based evaluation of wheat cultivars under graded nitrogen levels in North-West India - Gawdiya, Sandeep; Kumar, Dinesh; Sharma, Ramandeep Kumar (Frontiers in Agronomy, 2025)
Nutrients uptake by plants from the soil depends on the fertilizers applied, the physical and chemical properties of the soil, and various environmental and biological factors. Each nutrients have a positive or negative interaction with other nutrients in terms of their availability in the soil and their uptake in plants. The purpose of this study is to investigate the effects of successive increases in nitrogen (N) fertilizers on macronutrient uptake, system productivity (SP), and wheat equivalent yield (WEY) by wheat. This study was carried out in a split plot design with three distinct N input (N0, N75, and N150) in the main plot and ten wheat cultivars in the sub-plot over two consecutive years (2020-21 and 2021-22) in New Delhi, India. The highest SP of 9.85 t/ha-1, P & K uptake in grain (PUG) of 21.6 & 23.8 kg/ha-1, straw (PUS) of 13 & 106.4 kg/ha-1, and total phosphorus uptake (TPU) of 34.6 & 130.4 kg/ha-1 were obtained by the ‘HD 3249’ cultivar, followed by ‘HD 3117’. The application of N75 and N150 increased SP by 57.9% and 99.2%, WEY by 45.2% and 61.5%, PUG by 105.2% and 227%, PUS by 94% and 182%, and TPU by 100.5% and 208.7%, respectively, over N0. The study findings indicate that N fertilization positively influences macronutrient uptake in wheat, with cultivars ‘HD 3249’ and ‘HD 3117’ emerging as efficient candidates for optimizing macronutrient utilization. These cultivars hold significant potential for wheat breeding programs aimed at enhancing nutrient uptake while maintaining system productivity. Furthermore, incorporating biological nitrification inhibition traits into these cultivars is recommended to develop climate-smart wheat varieties.